The school is not white! : a true story of the civil rights movement - Rappaport, Doreen; James, Curtis, 1966- (New York : Jump at the Sun/Hyperion Books for Children, 2005)
Relates the true story of the Matthew and Mae Carter family, in simple text with illustrations, and how they helped to integrate an all-white school in Drew, Mississippi, in 1965, suffering years of name-calling, humiliation, and death threats.
Includes bibliographical references.
Booklist
Horn Book
6.2
3-6
Keywords: African Americans -- Education -- Juvenile literature; School integration -- United States -- Juvenile literature; Race relations -- United States -- Juvenile literature; Carter family -- Juvenile literature; African Americans -- Education; School integration; Race relations; Carter family; African Americans -- Education; School integration; Race relations; Carter family